Sistem Informasi Akademik Subsistem Master Data Mahasiswa Dengan Menggunakan Framework CodeIgniter - Irsyad Purbha Irwansyah (Jurnal Informatika: Jurnal Pengembangan IT, 2018)
In designing an academic information system in the wider scope, the first thing to be built is an information system that can process master data. Examples of such master data is student data, course data, and lecturer data. This student data becomes very important because student data will become a reference or data source for other information system incorporated in an academic information system as a whole which is found in Islamic University As-syafiiyah. To build an academic information system that capable of processing master data student required an adequate framework. Codeigniter is a very popular framework as it is very light and has very complete documentation making it easy to use. Codeigniter also uses the MVC approach (Model, View, Controller) in the concept of application development so it will be easier if the development of this information system is growing or transferable in the development process. Based on the above, it is necessary to develop an academic information system with master data subsystem of students at Islamic University As-syafiiyah which can manage all student data with Codeigniter framework.